Pengaruh Kemampuan dan Motivasi Terhadap Kinerja Guru SMA 6 Jeneponto - Israf Pangeran, M Aco; Musa, Muh. Ichwan; Ruma, Zainal (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
This research was conducted to determine whether ability and motivation have an influence on performance. The sample used in this study amounted to 64 teachers of SMA 6 Jeneponto which were divided into PNS and Non-PNS teachers. Then the data collection techniques carried out in this study used the method of observation and questionnaires. The data analysis technique used is multiple linear regression using Statisstical Product and Service Solution (SPSS).These results indicate that partially the ability variable (X1) has a positive and significant effect on teacher performance and the motivation variable (X2) has a greater positive and significant effect than the ability variable (X1). Simultaneously, the two independent variables, namely Ability (X1) and Motivation (X2) have a positive and significant effect on the dependent variable, namely Performance (Y).